Singapore’s leadership, circa 2004 - Softer, gentler, consultative? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Long before the ‘locals versus foreigners’ debate captured the imaginations of the nation, Singaporeans might faintly remember the ‘stayers versus quitters’ contention, as well as talk of ‘heartlanders versus cosmopolitans’ – milestones that are now neatly documented into a collection of essays, bundled in the book, Impressions of the Goh Chok Tong Years in Singapore. Stories ranging from Singapore’s population decline, bilateral relations and SARS crisis, to interethnic tensions, censorship and civil activism are captured, providing a remarkably wide, stereoscopic (if not nostalgic) peek into a recent past.